Prospects and problems of Malaysian cocoa beans [Theobroma cacao] - Shepherd, R. (Harrisons Malaysian Plantation Berhad, Kuala Lumpur) (MIFT, 2013)
Bean count, size uniformity, nib pH and lack of chocolate flavour had been identified as areas of drawbacks in Malaysian cocoa beans. Bean count and size variation were genetically controlled and in addition they were also affected by the soil type and climate. It would appear that very little could be done to the existing cocoa plantings for improving the situation. Planting of new clones now available would probably reduce these problems. Due to financial constraints, the fermentaries in general only carry out limited the acidity and lack of chocolate flavour in Malaysian cocoa beans, techniques had been evolved to reduce these problems. Some of these techniques were already in commercial practice. However, no single fermentation technique had proved to be the best. Research must continue on alternate techniques with the objective of developing methods appropriate to specific circumstances, including scale of operations